Correlação entre perfil lipídico, estado menopausal e câncer de mama - Altino, José (2012)
Introduction: Breast cancer has a high prevalence and mortality in women. The family history in first-degree relatives is the main risk factor for the disease, accounting for 20-25% of cases. The remaining cases are caused by multiple factors, such as obesity, dyslipidemia, use of hormone therapy (HT). However it is unclear the effect of the combination of these factors in breast cancer. Objective: To evaluate the relationship between hormone levels and lipid profile and its influence on the immunohistochemical expression of receptors in breast tumors in postmenopausal women with or without HT, and to assess some risk factors and prognosis of breast cancer. Casuistic and Method: We studied 50 post-menopausal women with breast cancer, divided into two groups: G1 without, and G2 - with HT, at least 5 years, with HT suspended for cancer diagnosis. We analyzed lipid profile including total cholesterol (TC) and fractions (LDLc, HDLc, VLDLc) and triglycerides (TG), and the hormonal profile (estradiol, follicle stimulating hormone (FSH) and luteinizing hormone (LH). The analysis of immunohistochemical expression comprised estrogen receptors (ER), progesterone (PR) and human epidermal factor type 2 (HER-2). We also evaluated the value prognosis of these receptors and the body mass index (BMI). Higher significance level of P <0.05 was considered. Results: Values of serum TC, LDLc, and HDLc were according to recommended limits in both groups (P> 0.05), while increased median values were observed for VLDLc and TG in G1 (36, 180 mg / dL, respectively ) versus G2 (28; 142 mg / dL, respectively, P = 0.048 for both). The presence of ER, PR, and HER-2 and itsrelationship with lipid profile and hormonal profile were similar between the groups (P> 005). The median values for hormone profile were similar in both groups (P> 005), except in the group analysis for LH values in pre-and postmenopausal women, especially the HT group, with 28% of patients with levels LH corresponding to premenopausal women (P = 0.010). A positive correlation was observed between levels of LDLc with CT. VLDLc, and TG for G1 (P ≤ 0.001) and G2 (P <0.05) positive correlation between TG and VLDLc in G1 (P <0.001) and G2 (P <0.001) negative correlation between the level of HDL-C and LH in G1 (P = 0.023); positive correlation between FSH and LDLc in G2 (P = 0.041), positive correlation between FSH and LH in G2 (P = 0.048); negative correlation between FSH and estradiol in G1 (P = 0.001). Risk factors (lipid profile and lipid BMI) and prognostic factors (absence of ER and PR, and presence or absence of HER-2) were similar in G1 and G2 for disease-free survival and overall (P> 0.05). Conclusion: Changes in hormonal and lipid profile did not influence the immunohistochemical expression of tumor tissue, prognostic factor in breast cancer, therefore, does not interfere with overall survival and free- tumor recurrence.